2004
DOI: 10.1021/np049831z
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Senecio chionophilus with Potential Antitubercular Activity

Abstract: Two new sesquiterpenoids, (1S,4S,5R,10R)-1-hydroxy-6-isobutyryloxy-10H-9-oxofuranoeremophilane (1) and 1alpha-hydroxy-6beta-(2xi-methylbutyryloxy)-10alphaH-9-oxofuranoeremophilane (2), along with 21 known constituents, were isolated from the n-hexane and dichloromethane extracts of the above-ground biomass and roots of Senecio chionophilus. The structures of 1 and 2 were elucidated on the basis of spectroscopic evidence and chemical transformation methods. The absolute configuration of 1 was determined by Mosh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…This is the first evidence that sesquiterpenoids of the furanoeremophilane type may be considered as potential antitubercular leads. In addition, the comparison of the antitubercular activities of betulinic, oleanolic, and ursolic acids, with MICs of 32, 64, and 32 mg/ml, respectively, with those of inactive analogues indicated that the presence of a COO group in a polycyclic triterpene skeleton appears to be necessary for the observed activity against M. tuberculosis [75].…”
Section: Pyrrolizidine Alkaloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first evidence that sesquiterpenoids of the furanoeremophilane type may be considered as potential antitubercular leads. In addition, the comparison of the antitubercular activities of betulinic, oleanolic, and ursolic acids, with MICs of 32, 64, and 32 mg/ml, respectively, with those of inactive analogues indicated that the presence of a COO group in a polycyclic triterpene skeleton appears to be necessary for the observed activity against M. tuberculosis [75].…”
Section: Pyrrolizidine Alkaloidsmentioning
confidence: 99%
“…The new macrocyclic PA 62 was isolated from the roots of S. uspallatensis, together with the previously known compound 41 [35]. From S. pterophorus, pterophorin (65), a new 152 6b-( Isobutyryloxy)-1a-(senecioyloxy)-10aH-furanoeremophilan-9-one S. panduriformis aerial parts [39] 153 2b-Hydroxy-6b-(isobutyryloxy)-1a-(senecioyloxy)-10aH-furanoeremophilan-9-one S. panduriformis aerial parts [39] 154 6b-( Senecioyloxy)furanoeremophil-1(10)-en-9-one S. lanceus aerial parts and roots [39] 155 6b-( Propionyloxy)furanoeremophil-1 (10) 190 6b-Acetoxy-la-(angeloyloxy)-10b-hydroxyfuranoeremophilan-9-one S. erosus aerial parts and roots [74] 191 1a-Acetoxy-6b-(senecioyloxy)-10aH-furanoeremophilan-9-one S. hypochoerideus roots [56] 192 1a-Acetoxy-6b-(isovaleryloxy)-10aH-furanoeremophilan-9-one S. hypochoerideus roots [56] 193 1a-Hydroxy-6b-(senecioyloxy)-10aH-furanoeremophilan-9-one S. hypochoerideus roots [56] 194 1a-Hydroxy-6b-(isovaleryloxy)-10aH-furanoeremo-S. hypochoerideus roots [56] philan-9-one S. chionophilus aerial parts and roots [75] 195 1a,6b-Dihydroxy-10aH-furanoeremophilan-9-one S. hypochoerideus aerial parts [56] 196 1a,6b-Dihydroxyfuranoeremophilan-9-one S. hypochoerideus aerial parts and roots 214 1a-Hydroxy-6b-[(2-methylbutyryl)oxy]-10aH-furanoeremophilan-9-one S. chionophilus aerial parts and roots [75] 215 6b-( Angeloyloxy)-1a-hydroxy-10aH-furanoeremophilan-9-one S. chionophilus aerial parts and roots [75] 216 1a-Hydroxy-6b-(isobutyryloxy)-10aH-furanoeremophilan-9-one S. chionophilus aerial parts and roots [75] 217 6b-( Propionyloxy)furanoeremophil-9-en-1-one S. pampse roots [45] 218 6b-Acetoxy-1a-hydroxy-10aH-furanoeremophilan-9-one S. pampse aerial parts [45] 219 1a,6b-Diacetoxy-10aH-furanoeremophilan-9-one S. pampse aerial parts [45] 220 3b-Acetoxy-6b-(tigloyloxy)furanoeremophilan-9-one S. pyranidatus aerial parts and roots [14] 221 3b-Acetoxy-6b-(angeloyloxy)furanoeremophilane S. pyranidatus aerial parts and roots [14] 222 3b-Acetoxy-6b-(tigloyloxy)furanoeremophilane S. pyranidatus aerial parts and roots [14] 223 3b-Acetoxy-6b-(senecioyloxy)furanoeremophilane S. Germacranes 454 9b-Acetoxy-3b-(angeloyloxy)-1b,10a:4a,5b-diepoxy-8b-(senecioyloxy)germacr-11-ene S. galpinii aerial parts and roots [90] 455 3b-( Angeloyloxy)-1b,10a : 4a,5b-diepoxy-8b-(senecioyloxy)germacr-11-en-9b-ol S. galpinii aerial parts [90] 456 5a,9b-Diacetoxy-3b,8b-bis(angeloy...…”
Section: Pyrrolizidine Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…eliciting food avoidance (Hägele and Rowell-Rahier, 2001). Some of these compounds exhibit cytotoxic (Gao et al, 2003;Wu et al, 2005;Zhang et al, 2005), antihyperglycemic (Inman et al, 1999), antimicrobial (Garduñ o- Ramírez et al, 2001;Wang et al, 2002;Gu et al, 2004;Mohamed and Ahmed, 2005), anti-inflammatory (Jimé nez-Estrada et al, 2006) or antioxidant activity (Doe et al, 2004(Doe et al, , 2005Shindo et al, 2004). It should also be noted that cacalolides are not sesquiterpenes, as is erroneously indicated (Doe 0939Ð5075/2007/0500Ð0362 $ 06.00 " 2007Verlag der Zeitschrift für Naturforschung, Tübingen · http://www.znaturforsch.com · D et al, 2004Shindo et al, 2004;Jimé nez-Estrada et al, 2006), since they do not hold to the isoprene rule.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the comparison of the NMR data as well as the physicochemical properties of the known compounds, the following compounds were identified as follows: 8b-hydroxyeremophila-3,7(11)-diene-8a,12(6a,14)-diolide (9) [23], 8b-methoxyeremophila-3,7(11)-diene-8a,12(6a,14)-diolide (10) [23], furoeremophil-3-en-14,6a-olide (11) [24], furoeremophilan-14b,6a-olide (12) [25], 1a-hydroxy-6b-isobutyroxy-9-oxo-(10bH)-furoeremophilane (13) [26], 1a-hydroxy-6b-isobutyroxy-9-oxo-(10aH)-furanoeremophilane (14) [26] [27], 6b-(angeloyloxy)-1a,10b-dihydroxy-9-oxofuranoeremophilane (15) -stigmasten-3-ol [31], daucosterol, 6-O-acetyl-a-d-glucopyranoside [32], and cerotic acid.…”
mentioning
confidence: 99%